A novel soybean flour as a cryoprotectant in freeze-dried Bacillus subtilis SB-MYP-1. (April 2017) - Mahidsanan, Thitikorn; Gasaluck, Piyawan; Eumkeb, Griangsak
Abstract: Bacillus subtilis SB-MYP-1 isolated from Thai Thua-nao fermentation has already been demonstrated as a potential starter culture. The aim of this work was to reveal the efficiency order of soy protein isolate (SPI), soluble starch (ST), maltodextrin (MD), and Doikham soybean flour (SBF) for protecting B. subtilis SB-MYP-1 cells under sub-lethal stress of freeze-dried encapsulation. The combination criteria, including the survival rate, low water activity, and moisture content of freeze-dried cells with SBF, were approximately 63.72% (1.30 × 10 8  CFU/g as cell viability), 0.285, and 2.31% wet basis, respectively, which were relative to the standard quality of powdered starter culture. In addition, the cell membrane fluidity, metabolic retardation, activities of three intracellular enzymes (glutamate dehydrogenase, GDH; 2-oxoglutarate aminotransferase, GOGAT; and glutamine synthetase, GS), and pgsB gene expression of freeze-dried cells were maintained by SBF protection. Surprisingly, the mode of action of SBF could preserve the protein stabilization, phospholipid bilayer, and peptidoglycan surface in freeze-dried cells, whereas the partial cell surface and lipid bilayer of cells with SPI, ST and MD were destroyed after sub-lethal freeze drying. This study revealed the novel application of SBF as a cryoprotective agent for further freeze-dried B. subtilis SB-MYP-1 preservation. Highlights: A novel soybean flour (SBF) cell protection mechanism was successfully revealed. SBF is a new freeze-dried B. subtilis SB-MYP-1 cell (FDBSC) protective agent. SBF effectively maintained the highest survival of FDBSCs (>10 7  CFU/g). SBF could preserve the cell wall and membrane fluidity of FDBSCs. pgsB gene of FDBSCs with SBF was still expressed.